Escalation of real wages in Bangladesh: Is it the beginning of structural transformation? - Zhang, Xiaobo; Rashid, Shahidur; Kaikaus, Ahmad; Ahmed, Akhter (University Press Limited, 2021)
With about 1,200 people per square kilometer, Bangladesh is one the most densely populated countries on the planet. The reality of intense population pressure is reflected in commonly portrayed images in the popular media, such as crowded buses and trains with passengers on top, endless lines of human-powered rickshaws, and deaths in the thousands from both natural and man-made disasters. With increasing landlessness, and a heavy reliance on labor markets, understanding the dynamics of wage formation in this setting is critically important for identifying the process of economic transformation and poverty reduction. However, both theories and empirics of wage determination in Bangladesh, and elsewhere in developing countries, have intrigued economists for decades. The neoclassical theories, where labor demand and wages are determined by the marginal physical product, cannot explain stable wages amid seemingly unlimited supply of workers and massive involuntary unemployment in developing countries like Bangladesh. The reason is simple: if market clearing conditions hold, unemployed workers should bid down wages until full employment as reached. One set of theories that provide a more coherent explanation of stable wages amid abundant labor supply has been the nutrition-based efficiency wage theory, originally proposed by Leibenstein (1957) and Mazumdar (1959). The premise of this theory is that since productivity depends on consumption, it is in the interest of the employers to pay a wage that ensures minimum calorie requirement of the workers so that they can work effectively.